(untitled) (Swiss Medical Weekly, 2022)
INTRODUCTION: Congenital heart disease (CHD) is the most frequent birth defect. As survival has significantly improved, attention has turned to neurodevelopmental outcomes of children undergoing heart surgery in early infancy. Since multiple risk factors contribute to neurodevelopmental alterations, a nationwide registry collecting data on medical characteristics, interventions, clinical course and neurodevelopment until school-age is needed to improve the quality of management, identify risk- and protective factors affecting neurodevelopment, and facilitate multicentre trials. METHODS AND ANALYSIS: The Swiss Outcome Registry for CHIldren with severe congenital heart Disease (ORCHID) is a nationwide, prospective, population-based patient registry developed (1) to collect baseline characteristics and clinical data of CHD patients operated with bypass-surgery or hybrid procedures in the first 6 weeks of life in Switzerland, (2) to monitor long-term neurodevelopment, and (3) to relate clinical characteristics and neurodevelopment to identify risk and protective factors in these children. This registry started data collection relating to pregnancy, birth, preoperative course, catheter-based and surgical treatment, postoperative course and reinterventions in 2019. The primary outcome includes standardised neurodevelopmental assessments at 9 to 12 months, 18 to 24 months and 5.5 to 6 years. We expect to include 80 to 100 children per year. Correlation and regression analyses will be used to investigate risk- and protective factors influencing neurodevelopment. ETHICS AND DISSEMINATION OF RESULTS: Swiss ORCHID received support by the Accentus Charitable Foundation, the Anna Mueller Grocholoski Stiftung, the Swiss Society of Paediatric Cardiology, the Verein Kinderherzforschung, and the Corelina – Stiftung für das Kinderherz, and was approved by the cantonal ethics committees. Findings will be presented at national and international scientific meetings, and published in peer-reviewed journals. Results will also be shared with patient organizations, primary health care providers, and public health stakeholders to ensure a widespread dissemination of the results.